Integration and completion: life wisdom and happiness of Chinese older adults from a life course perspective - Cheng, Sheng-Li; Zhang, Xin; Liu, Shushan; Zhao, Chenxu; Bi, Sizhen (Frontiers in Public Health, 2025)
IntroductionLife course theory posits that historical events that transpired in the past shape an individual’s well-being. In the last century, China experienced a series of significant events in rapid succession, including the Anti-Japanese War (AJW), the Civil War (CW), the Great Famine (GF), the Cultural Revolution (CR), and the Reform and Opening of China (ROC). These early life experiences may have lasting effects on older adults. Concurrently, given the discrepancies in life course, there may be discrepancies in well-being and perceptions of life between Chinese and Western older adults.MethodsA qualitative study was conducted within a constructivist paradigm. In-depth interviews were carried out with 16 older adults using a standardized inventory. A theoretical framework was constructed through the effects of temporary breakdown on the life course and “vital involvement in the necessary disinvolvements of old age (VINDOA).” Data were coded using the Nvivo-12 software.ResultsThe themes of well-being and life wisdom among Chinese older adults centered on (1) valuing education, strong family ties, and active social participation, which were associated with personal experiences of well-being. (2) Satisfaction and gratitude for social welfare, being happy and worried about current social situation in the same time, which are related to older adults’ values of society. (3) Expectations, encouragement, and transmission of wisdom to youth are related to their views of young people and youthfulness.Conclusion and discussionA key finding is that how older adults perceive life strongly influences their present experiences and sense of well-being. In addition, the social class in which older people live plays an important role in the connection between a challenging past and a fulfilling present. Furthermore, social development has a positive impact on the well-being of older adults, while the level of social participation of older adult people exerts a further influence on their own well-being and their capacity to contribute to society.